Infection of plants with bulging nematodes - Matmuratova Gulnoza Baxtiyarovna; Avalbaev Olimjon Narkuzievich; Mavlonova Sunajon Xujayazovna (Research Parks Publishing LLC, 2021)
Pathological changes are observed mainly in the root part of cotton infected with bulging nematodes. As a result of the development of larval nematode larvae and the formation of giant cells, the function of the conductive tissue in the plant root is impaired. As a result, moisture and nutrients are spent on the larvae of bulging nematodes. As a result, crop yields are sharply reduced.